CONSUMER PERCEPTION TOWARDS CLOUD KITCHEN - Mohd Syafiq Bin Othman; Fatin Syahira Liana Badaruddin; Nik Mohd Shahril Nik Mohd Nor (Journal of Islamic, Social, Economics and Development, 2022)
Throughout the year, the innovations keep on changing according to thetechnologies. Malaysia had started the cloud kitchen system during the Covid-19 outbreak.However, not everybody knows the existence of cloud kitchen. The purpose of this study is todetermine the relationship between the performance expectancy, effort expectancy, socialinfluence and facilitating conditions on cloud kitchen. A quantitative research methodology viaonline survey was carried out. A convenience sampling technique of 403 potential customershad answered the survey. Data obtained were analysed using statistical software, StatisticalPackage for the Social Science (SPSS) version 21.